2004
DOI: 10.1007/s00467-004-1418-z
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical markers of bone metabolism and calciuria with inhaled budesonide therapy

Abstract: We investigated the changes in renal excretion of calcium, sodium, and potassium in asthmatic children treated with inhaled budesonide, an inhaled glucocorticoid. Twenty-two asthmatic patients (7 female, 15 male, mean age 10.1+/-4.3 years) treated with 400-600 microg/day inhaled budesonide and 23 healthy children (6 female, 17 male, mean age 10.2+/-2.8 years) were enrolled in the study. The parameters recorded were serum sodium, potassium, calcium, phosphorus, alkaline phosphatase (ALP), type I collagen carbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…As an example, Boot et al (30) did not find differences in mean osteocalcin, PICP, and ICTP levels between asthmatic children treated with ICS and controls. In contrast, Akil et al (28) found a significant decrease in osteocalcin and increase in ICTP levels compared with pretreatment values in a study in 22 asthmatic children. Also, in the study comparing high-dose with low-dose fluticasone propionate, significant initial reductions in osteocalcin and PINP levels were noticed without a difference in effect on BMD (12).…”
Section: Discussionmentioning
confidence: 79%
“…As an example, Boot et al (30) did not find differences in mean osteocalcin, PICP, and ICTP levels between asthmatic children treated with ICS and controls. In contrast, Akil et al (28) found a significant decrease in osteocalcin and increase in ICTP levels compared with pretreatment values in a study in 22 asthmatic children. Also, in the study comparing high-dose with low-dose fluticasone propionate, significant initial reductions in osteocalcin and PINP levels were noticed without a difference in effect on BMD (12).…”
Section: Discussionmentioning
confidence: 79%
“…Akil et al reported that biochemical markers of bone metabolism were not significantly different between controls and asthmatic children [ 28 ].…”
Section: Discussionmentioning
confidence: 97%
“…There are good examples where the concentrations of the endogenous protein or its soluble forms are increased because of a compensatory mechanism. [7][8][9][10] Investigation will be warranted in such scenarios. An understanding of the biology behind the therapeutic, including the compensatory mechanisms, can help defi ne the investigation that should be used in examining the specifi city of a particular method.…”
Section: Challenges Of Lba For Specificity and Selectivity Evaluationsmentioning
confidence: 99%